"A Bad Kind of Magic": The Niebuhr Brothers on "Utilitarian Christianity" and the Defense of Democracy. (31st January 2014) - Gaston, K. Healan
<x content-type="archive" xml:space="preserve">Abstract</x> In August 1947, a few months after President Harry S. Truman pledged the United States to fight communism around the globe, Time magazine delivered a stern warning to its wide readership from Reinhold Niebuhr, the nation's best-known theologian: "The new idolatry in the U.S. may be a blind, uncritical worship of democracy." The Time article excerpted a Christianity and Crisis piece on "Democracy as a Religion" in which Niebuhr stressed the hidden dangers of the increasingly ubiquitous paeans to democracy in postwar America. That spring's commencement addresses, he noted, would give any sensible observer the distinct impression that "Americans have only one religion: devotion to democracy. They extol its virtues, are apprehensive about the perils to which it is exposed, pour maledictions upon its foes, rededicate themselves periodically to its purposes and claim unconditional validity for its ideals."